2015
DOI: 10.1016/j.gsf.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Importance of initial buoyancy field on evolution of mantle thermal structure: Implications of surface boundary conditions

Abstract: a b s t r a c tAlthough there has been significant progress in the seismic imaging of mantle heterogeneity, the outstanding issue that remains to be resolved is the unknown distribution of mantle temperature anomalies in the distant geological past that give rise to the present-day anomalies inferred by global tomography models. To address this question, we present 3-D convection models in compressible and self-gravitating mantle initialised by different hypothetical temperature patterns. A notable feature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 96 publications
(145 reference statements)
3
15
0
Order By: Relevance
“…The dynamical importance of deep-mantle upwellings, extracting up to 20 TW from CMB ( 44 , 50 ), is compatible with recent estimates of high CMB heat flux drawn from the core that are derived from mineral physical arguments ( 16 , 17 ). High heat transport across the CMB would also account for up to approximately 50% of the heat flux at the top of the mantle ( 12 ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The dynamical importance of deep-mantle upwellings, extracting up to 20 TW from CMB ( 44 , 50 ), is compatible with recent estimates of high CMB heat flux drawn from the core that are derived from mineral physical arguments ( 16 , 17 ). High heat transport across the CMB would also account for up to approximately 50% of the heat flux at the top of the mantle ( 12 ).…”
Section: Discussionsupporting
confidence: 85%
“…From the perspective of the predicted plate motions, the main difference between the V1 and V2 viscosities is that the latter has a thicker, higher viscosity lithosphere, which reduces the plate velocities (reflected in a reduced fit; see Table 1). From the perspective of deeper flow dynamics, the V2 profile has a higher viscosity in the bottom half of the lower mantle, yielding a more stable deep-mantle flow that has been extensively explored in the past numerical simulations of very long-term mantle convection ( 44 , 50 , 51 ). Unless otherwise specified, all mantle flow predictions discussed below use the V2 profile.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute viscosity at middle lower mantle depths (Figure c) is higher than anywhere else in the mantle, and the lateral variations are mainly characterized by local zones of relatively reduced viscosity. These regions are related to hotter‐than‐average upwellings beneath West Africa, South Africa, West Pacific, and South‐East Pacific that are detected in tomography‐based convection models [ Glišović et al , ; Glišović and Forte , ]. Our calculations also show two large‐scale regions of low‐viscosity ∼10 21 Pa s at the top of the D " layer that are associated with LLSVPs (Figure d).…”
Section: Resultssupporting
confidence: 63%
“…Three types of surface boundary conditions (free‐slip, no‐slip, or plate velocity boundary conditions) can be assumed. Previous studies that have investigated these three types of surface boundary conditions have suggested that free‐slip boundary conditions provide the best fit to the geoid in comparison with the other two types [ Glišović and Forte , ; Thoraval and Richards , ]. Using the HC code, we use free‐slip boundary conditions at the surface and core‐mantle boundary and compute instantaneous flow associated with the present‐day inferred mantle density distributions.…”
Section: Methodsmentioning
confidence: 99%